2018
DOI: 10.4236/ojoph.2018.82011
|View full text |Cite
|
Sign up to set email alerts
|

Haemogram Parameters in the Development of Retinopathy of Prematurity

Abstract: Purpose: Retinopathy of prematurity (ROP), an abnormal proliferation of retinal vessels in premature infants with low birth weight, develops due to many factors. This study investigated a possible correlation between haematological parameters and ROP development. Method: This study included 189 infants without ROP and 128 with ROP. All were born at 35 weeks' gestation or earlier, had a CBC drawn within 72 hours of birth, and had haemogram data for the first month. Haemoglobin (Hb), haematocrit (Hct), mean corp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…The most significant factors are oxidative stress caused by oxygen (O 2 ) and O 2 metabolites [1,2] and associated inflammation [3]. Studies demonstrating that Hb and Hb products, as well as haemogram parameters, are responsible for O 2 transport can be effective on ROP in infants, as they support the role of oxidative stress in ROP development [4].…”
Section: Introductionmentioning
confidence: 99%
“…The most significant factors are oxidative stress caused by oxygen (O 2 ) and O 2 metabolites [1,2] and associated inflammation [3]. Studies demonstrating that Hb and Hb products, as well as haemogram parameters, are responsible for O 2 transport can be effective on ROP in infants, as they support the role of oxidative stress in ROP development [4].…”
Section: Introductionmentioning
confidence: 99%
“…In studies conducted so far, the most critical risk factor for ROP was found to be retinal vascular immaturity determined by low gestational age (GA) and low birth weight [2] [3] [4] [5]. Other risk factors include oxygen toxicity, acidosis, intraventricular hemorrhage, patent ductus arteriosus, sepsis, hyperbilirubinemia, low Apgar score, mechanical ventilation, and blood transfusion [6] [7] [8]. However, other preventable factors are still being investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the Hieroglyphic Luwian inscriptions found to the north of the Kızılırmak River have been known for a very long time (for KARABURUN see already Anderson 1901, for ÇALAPVERDİ 1-2 Forrer 1927 who already talks about Tabalite inscriptions, for ALİŞAR Gelb 1935: 73), the only exceptions being the KIRŞEHİR-letter, found and published not long ago (Akdoğan/Hawkins 2007-08 and) and a further fragment, that may or may not belong to this letter . However, until today, most of the publications, not only those written by non-specialists, but also Hittitologists, mark the northern border of Tabal with the river called Kızılırmak (without any argumentation).…”
Section: Introductionmentioning
confidence: 99%